Advantages and disadvantages of current reference and digital objects linking models in scientific information space - Vrana, Radovan (Array, 2003)
The aim of this paper is to present some of the advantages and disadvantages of a selection of current reference and digital objects linking models in scientific information space. The growth of electronic information resources and electronic journals in particular, introduced a new set of problems to scientists who are trying to find a way to access information written in footnotes and references of published scientific works in printed as well as in electronic format. In his paper on of electronic journals on scholarly communication, Harter came to conclusion that almost 50% percent of online resources are not directly accessible from the information provided in references (Harter, 1996). This means that scientists as readers are deprived of possibility to speed up their discovery of information relevant to their work because they lack instruments for the direct access to information resources found in references in electronic form. This also means that the value of electronic publications is diminished by not using their full potential for information access and use. To alleviate this problem, several concepts are being developed.